Implementation of Digital Health Services to Improve Public Health: Challenges with the JKN Mobile App - Mufidah, Nabila Haninda; Larasati Putri, Herananda Dewi; Schwermer, Leon; Sajida, Rania Hanin (Journal of Social Dynamics and Governance, 2025)
Mobile is an application launched by BPJS Health that can be downloaded on a smartphone. The purpose of this research is to understand how the JKN application works and to identify the challenges encountered during the implementation of JKN Mobile in Indonesia. The focus of the discussion is to delve deeper into JKN in Indonesia and assess its impact on society. The method used is a literature review (SLR), which examines various information about JKN in scientific articles and related sources relevant to the research being discussed. Based on the research results, it was found that there are still many obstacles to implementing JKN, such as people who do not want to use the JKN application. This application depends on the signal and network, so there are some areas where the network is weak, and logging in to the JKN application is difficult.